Gavin Lambert's Another sky - Lambert, Gavin 1924-2005; Lassally, Walter 1926-2017; Grayson, Victoria ca. 20. Jh; Lacey, Catherine 1904-1979; Montague, Lee 1927-2025; Forbes, Alan 20. Jh (Facets Video, 2007)
"Rose, a demure and prim governess, arrives in Marrakesh to begin a new job as a paid companion to a wealthy English expatriate. As she explores the exotic environs of her new home, she is seduced by the men, music, and mystery of Morocco.The only film directed by screenwriter and film critic Gavin Lambert "Another sky" was inspired by Lambert's peer and friend, Paul Bowles (The Sheltering Sky). The dreamy black and white cinematography by Walter Lassally captures the steamy atmosphere of North Africa in the 1950s, where a colony of expatriate artists and writers thrived in a bohemian existence." [cover]
fullscreen
Orig.: Großbritannien 1954
Enth. "Gavin Lambert remembered", a documentary short ; side-by-side comparison between original & restored version ; collectible booklet